Cost-benefit analysis explained. (June 2015) - Liddle, John; Wright, Matt; Koop, Bronte
In every evaluation context, the question of worth underpins the motivation or role of the evaluation, even if it is not explicitly stated. Often, this question cannot be answered fully, simply because people or parties may make varying subjective judgments about the value and likelihood of different outcomes—it is at this juncture that cost–benefit analysis (CBA) can be of use. For evaluations where most significant inputs and outcomes can be valued in monetary terms, CBA provides a systematic methodology for reaching conclusions on 'worth'. CBA is best used in conjunction with traditional evaluation approaches rather than as a replacement approach. The use of CBA can help an evaluator to be more confident in stating the evaluation findings, particularly in social policy settings where the use and importance of CBA is growing. This article aims to help evaluators learn more about CBA by demonstrating its use to analyse an intervention designed to help young people disengaged from learning.